Mediation as an Alternative to Medical Dispute Settlement in Hospitals - Banjarnahor, Hotma; Helvis, Helvis (Fakultas Syariah INSURI Ponorogo, 2023)
Mediation is one way to try to solve a disagreement. In this process, both sides agree to bring in a neutral third party to act as a mediator.The purpose of this research is to examine the case of Deed of Peace No. 001/AP/III/2021, in which a lawsuit was filed against the doctor due to malpractice that resulted in the death of the patient. As for the method that researchers uses an empirical legal approach, and the type of legal study is a full analysis of primary, secondary, and tertiary legal materials. The research and talk about it have led to a scientific work that is complete, clear, detailed, and well organized. Empirical Legal Research is a legal research method that uses empirical facts derived from human behavior, including both verbal behavior obtained through interviews and direct observation of real behavior. Empirical research is also used to look at the results of people's actions by looking at physical remains and old records. The results of this study are the constraints on the implementation of malpractice settlements in Deed of Peace No. 001/AP/III/2020 that are internal and external. Obstacles from within (internal) in the form of a lack of commitment and intention on the parties' part to reconcile While the inhibiting factors from outside (external) are the inability of the mediator to reconcile, the existence of advocates who seek profit by choosing the court route, and the absence of a special institution that is domiciled as a legal institution in each hospital, such as hospital ethics and law committees.